FIRE PREVENTION AND FIRE EXTINGUISHER USE TRAINING FOR HEALTHCARE AND NON-HEALTHCARE EMPLOYEES AT SEMBIRING GENERAL HOSPITAL - Herlina Jamaluddin EL- Matury (Jurnal Pengabdian Masyarakat Putri Hijau, 2026)
Hospitals are healthcare facilities with a high risk of fire hazards due to the use of medical equipment, electrical installations, chemical materials, and medical gases. This condition requires the preparedness of all employees, including healthcare and non-healthcare personnel, in fire prevention and early fire response. This community service activity aimed to enhance the knowledge and skills of employees at Sembiring General Hospital regarding fire prevention and the proper and safe use of Portable Fire Extinguishers (PFE). The implementation methods included theoretical lectures on potential fire hazards and fire classification, introduction to types of fire extinguishers, as well as simulations and hands-on practice in using PFE. The results indicated an improvement in participants’ understanding and skills in performing initial fire suppression actions. This training is expected to increase staff preparedness and support the creation of a safe and responsive hospital environment in emergency fire situations.